66.0k views
4 votes
Hi.

Please i need help with these questions :

Simplify
1.

\frac{ {d}^(2) - 9 }{ {d}^(2) - 7d + 12 }
2.

\frac{ {m}^(2) + 2mn + {n}^(2) }{ {m}^(2) - {n}^(2) }
3.

\frac{ {x}^(2) + xy - 6 {y}^(2) }{ {x}^(2) - 3xy + 2 {y}^(2) }


User Kyrsten
by
4.8k points

2 Answers

2 votes

1)


(d^2 - 9)/(d^2 - 7d + 12) = ((d - 3)(d + 3))/((d - 3)(d - 4)) = (d + 3)/(d - 4)

2)


(m^2 + 2mn + n^2)/(m^2 - n^2) = ((m + n)(m + n))/((m - n)(m + n)) = (m + n)/(m - n)

3)


(x^2 + xy - 6y^2)/(x^2 - 3xy + 2y^2) = ((x + 3y)(x - 2y))/((x - y)(x - 2y)) = (x + 3y)/(x - y)

User Hossein Fti
by
4.6k points
3 votes

Solutions :

1.
\bf \frac{ {d}^(2) - 9 }{ {d}^(2) - 7d + 12 }


\tt : \implies \frac{ {d}^(2) - (3)^(2) }{ {d}^(2) - 3d - 4d + 12 }

By using identinty a² - b² = (a + b)(a - b) in numerator and splitting method in denominator :


\tt : \implies \frac{ (d+3)(d-3) }{ {d}^(2) - 3d - 4d + 12 }


\tt : \implies ( (d+3)(d-3) )/(d(d - 3) - 4(d - 3))


\tt : \implies \frac{ (d+3)\cancel{(d-3)} }{\cancel{(d - 3)}(d - 4)}


\tt : \implies (d+3)/(d - 4)

Hence, answer is
\boxed{\bf (d+3)/(d - 4) }

________________________________

2.
\bf \frac{ {m}^(2) + 2mn + {n}^(2) }{ {m}^(2) - {n}^(2) }

By using identinty a² + 2ab + b² = (a + b)² in numerator and a² - n² = (a + b)(a - b) in denominator :


\tt : \implies ((m+n)^(2))/((m+n)(m-n))


\tt : \implies \frac{\cancel{(m+n)}(m+n)}{\cancel{(m+n)}(m-n)}


\tt : \implies (m+n)/(m-n)

Hence, answer is
\boxed{\bf (m+n)/(m-n)}

________________________________

3.
\bf \frac{{x}^(2) + xy - 6{y}^(2)}{{x}^(2) - 3xy + 2{y}^(2)}

By using splitting method in both numerator and denominator :


\tt : \implies \frac{{x}^(2) + 3xy - 2xy - 6{y}^(2)}{{x}^(2) - xy - 2xy + 2{y}^(2)}


\tt : \implies (x(x + 3y) - 2y(x + 3y))/(x(x - y) - 2y(x - y))


\tt : \implies \frac{\cancel{(x-2y)}(x + 3y)}{\cancel{(x-2y)}(x - y)}


\tt : \implies (x + 3y)/(x - y)

Hence, answer is
\boxed{\bf (x + 3y)/(x - y)}

User King Of Masses
by
4.9k points